NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI KEKELUARGAAN BATAK ANGKOLA - Rosmaimuna Siregar (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2018)
AbstractIndonesia is a multicultural country, having diverse ethnicities, races, cultures, languages, religions and so on. The Angkola Batak is a part of the Batak ethnic group in Indonesia that is no less unique and rich in culture ranging from language, social systems, family systems and philosophy of life that they uphold. Angkola Batak tribes are from North Sumatra, precisely in the southern part of Tapanuli. Among the several Batak tribes in North Sumatra, the Angkola Batak tribe is a tribe whose people have been acculturated with Islamic culture, so that the education system is also influenced by the tradition of the Angkola Batak tribe or vice versa. Thus it is very urgent to study the values of Islamic education contained in the tradition of his freedom.